INFLUENCE OF SERVICE QUALITY AND BRAND IMAGE ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Azizi, Putri; Asmaria Putri, Della; Fitri Sopali, Mardhatila; Brama Kumbara, Vicky (Jurnal Ipteks Terapan, 2022)
This study aims to determine the effect exchange rate, Service Quality and Brand Image of Customer Loyalty with Customer Satisfaction As a variable intervening for customers of Kupi Batigo Gor H. Agus Salim Padang, both in a joint and joint manner.The sample in this study were 100 customers at the Batigo Gor Kup H. Agus Salim Padang, the method of data analysis used multiple regression analysis and path analysis with the SPSS 21 application.The results showed that : 1) partially, there is no positive and significant influence between Service Quality on Customer Satisfaction. 2) There is no positive and significant influence between Brand Image and Consumer Satisfaction. 3) There is no positive and significant influence between customer satisfaction on customer loyalty. 4) There is a positive and significant influence between Service Quality on customer Loyalty. 5) There is a positive and significant influence between Brand Image and Customer Loyalty